Twenty years of mortgage banking in Slovakia - Eva Horvátová (International Journal of Financial Studies, 2020)
Mortgage banking began to develop in Slovakia after 1998 as an ambitious project, the goal of which was to elevate the lagging development of the real estate market, the development of the financial market and the creation of banks' long-term resources. Our goal is a comprehensive assessment of the development of Slovak mortgage banking for the past 20 years from the perspectives of the development of banking, the mortgage bond market, the real estate market and selected interactions between individual elements of the mortgage system. The specific aim of the study is to evaluate the substantial links between the basic economic indicators, indicators of housing finance and real estate prices in Slovakia. To evaluate these issues VAR (Vector Autoregression) models, models of panel and linear regression and DEA (Data Envelopment Analysis) models were used. Slovakia has specific indicators of the development of mortgage banking, adequate to its historical and economic development. It was confirmed that the availability of real estate loans had a significant impact on the increase in real estate prices. Real estate prices in Bratislava have different development factors than real estate prices from a nationwide perspective. Low interest rates have an important role in housing financing. The second part of the study is oriented towards an evaluation of the technical efficiency of individual banks. The results of DEA point out that the largest banks in Slovakia were the most efficient in the pre-crisis year 2007. The overall results show that policymakers should react not only to the household indebtedness rate and risks for individual clients, but should also see the risks for banks in possible changes in the real estate market, or the risks of changes in interest rates in the future.
Keywords: G21; G28; R31; 330; housing credits; interest rates; real estate prices